Romania : Recent Economic Developments and Selected Background Studies. (IMF Staff Country Reports; Country Report, 1996)
This Recent Economic Developments and Selected Background Studies paper on Romania provides an overview of key monetary and real sector developments in 1995, including the impact of agricultural credit on monetary control, the factors behind the growth in foreign currency credit, and the link between the current account deterioration and real sector developments. The paper examines fiscal policy and performance in the context of the tax reforms and improvements in expenditure management during the transition period, including progress in bringing implicit and 'off-balance sheet' subsidies within the scope of budgetary policy.